Computed air myelography of the lumbosacral spine. - Tan, W S; Spigos, D G; Khine, N; Capek, V (American Journal of Neuroradiology, 1983)
Plain computed tomography (CT) of the lumbosacral spine may be a reliable method for diagnosing herniated disk when abundant epidural fat is present. When epidural fat is not sufficient, CT after the administration of nonionic contrast medium (170 mg I/ml) and/or regular metrizamide myelography have been used. Ten patients were studied by CT enhanced with air injected as a negative contrast agent. The findings were correlated with plain and contrast-enhanced (metrizamide) CT as well as conventional myelography. The technique is described and advantages and disadvantages of the method are discussed. Air-contrast CT is useful in the evaluation of herniated disk in cases with equivocal findings on plain CT and in patients with a history of allergic reaction to iodinated contrast media.